Prediction of central compartment nodal metastases in papillary thyroid cancer using TI-RADS score, blood flow, and multifocality. (October 2022) - Yang, Jin-Ru; Song, Yan; Chang, Shu-Juan; Shi, Li-Li
Background: The relationship between the American College of Radiology (ACR) Thyroid Imaging Reporting and Data System (TI-RADS) and the risk of lymph node metastases in papillary thyroid cancer (PTC) could improve the detection rate of lymph node metastases in thyroid cancer and provide a scientific basis for clinical diagnosis. Purpose: To evaluate the risk of lymph node metastases of PTC associated with the score from ACR TI-RADS adjusted for other correlative factors. Material and Methods: A total of 560 patients with pathologically confirmed PTC were included in the study and classified into a metastases group and a non-metastases group. Clinical and pathological manifestations of the patients were collected. Results: The median TI-RADS score was 13 (p25 –p75 = 11–14) among the patients with lymph node metastases, higher than those without metastases 9 (8–10) ( P  < 0.001). Multiple logistic regression indicated that TI-RADS score (odds ratio [OR] = 2.204), male sex (OR = 2.376), multifocality (OR = 4.170), and rich blood flow (OR = 3.656) were risk factors for lymph node metastases in patients with thyroid carcinoma. Some related factors such as TI-RADS score, age(<45years old), male, multifocality and rich blood flow were related to lymph node metastases in the central area of the neck which could provide therapeutic strategy for further treatment. Conclusion: it is not just the TI-RADS score but also multifocality, blood flow, and sex that influence the prediction of the risk of PTC central lymph node metastases.